Effect of dietary dried milky sludge on productive performance and egg quality in laying Japanese quails - Tawadchai Suppadit (2018)
The experiment was conducted to study the effectiveness of dried milky sludge (DMS) as a feed source for laying Japanese quails. The DMS was incorporated into the experimental diets at levels of 0, 5.0, 10.0, 15.0 and 20.0%. Four hundred quails were used in a completely randomized design. The results revealed that the daily egg-laying rate, feed cost/100 egg weight, egg width, egg length, egg weight, shell quality characteristics in terms of breaking time, Young's modulus, work, max force, fracturability, breaking stress, stiffness and power, as well as color intensity and yolk height improved significantly with increasing levels of DMS in the diet (P < 0.05), while feed intake/bird/day, mortality and eggshell thickness showed no significant differences (P > 0.05). From this experiment, it was found that DMS incorporated into the experimental diet at the 20.0% level yielded the most productive performance and best egg quality. © 2009 Japanese Society of Animal Science.